ChemInform Abstract: A Simple Synthesis of 2‐[(Arylmethylidene)hydrazinylidene]‐3‐hydroxy‐4H‐furo [3, 2‐c]pyran‐4(3H)‐ones. Issue 35 (8th August 2013) - Adib, Mehdi; Ansari, Samira; Zhu, Long‐Guan; Rahimi‐Nasrabadi, Mehdi
Abstract via a three‐component reaction of 3‐acetylpyran‐2, 4(3H)‐dione, (isocyanoimino)‐triphenylphosphorane and aromatic aldehydes